2000
DOI: 10.1001/jama.284.16.2084
|View full text |Cite
|
Sign up to set email alerts
|

State Scholarship, Loan Forgiveness, and Related Programs

Abstract: In 1996, states fielded an obligated primary care workforce comparable in size to the better-known federal programs. These state programs constitute a major portion of the US health care safety net, and their activities should be monitored, coordinated, and evaluated. State programs should not be omitted from listings of safety-net initiatives or overlooked in future plans to further improve health care access. JAMA. 2000;284:2084-2092.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 13 publications
0
81
1
Order By: Relevance
“…In order to record and compare trends in state support-for-health service programs over time we reviewed and utilized where possible the methodology previously reported by Pathman et al [19]. This previous study of state loan and scholarship programs identified five different program categories (scholarship, loan, resident support, loan repayment, and direct financial support), and we have done likewise.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to record and compare trends in state support-for-health service programs over time we reviewed and utilized where possible the methodology previously reported by Pathman et al [19]. This previous study of state loan and scholarship programs identified five different program categories (scholarship, loan, resident support, loan repayment, and direct financial support), and we have done likewise.…”
Section: Methodsmentioning
confidence: 99%
“…Compendia included online sources and other available documents; previous studies; lists of state primary care office directors and administrators; lists of state loan repayment program contacts; officials in state offices of rural health and primary care, state public health offices and state higher education financial aid authorities, and other online sources, printed materials and documents available to the public. Our eligibility criteria for programs were determined using similar methods established by Pathman et al [19]. Eligible programs were designated as those that 1) provided financial support to students, resident or practicing physicians (MD or DO), physician assistants (PA), nurse practitioners (ARNP), certified nurse midwives, dentists, and licensed mental healthcare providers (e.g.…”
Section: Identifying Eligible State Programsmentioning
confidence: 99%
See 3 more Smart Citations